GENITAL SELF-MUTILATION IN DEPRESSION: A CASE REPORT - Rao, K. Nagaraja (Medknow Publications, 2002)
Genital self-mutilation is a rare severe form of self-injurious behaviour usually described in psychotic disorders with delusions & hallucinations. It has been ascribed to sexual conflicts, body image distortion, internalized aggression and suicidal intent. This phenomenon has been described in schizophrenia, affective psychosis, alcohol intoxication and personality disorders. In the present case genital self-mutilation in a case of Major-Depressive Disorder in an 82 yrs old male is being reported and psychosocial factors are discussed. This case has some unusual features.